Catheter Ablation of Paroxysmal and Persistent Atrial Fibrillation in Patients with Secondary Atrial Septal Defect. Evaluation of the Results and Impact on the Quality of Life - Myroslav M. Petkanych (Ukrainian Journal of Cardiovascular Surgery, 2023)
Introduction. The presence of atrial fibrillation (AF) in patients with secondary atrial septal defect (ASD) has significant impact on their quality of life (QoL) and reduces life expectancy. Current guidelines recommend catheter ablation (CA) for patients with AF in case of medical treatment failure, however, its use in patients with AF and ASD is still poorly studied.The aim. To study the efficacy and safety of CA and its impact on the QoL in patients with AF and secondary ASD.Materials and methods. In 2003-2023, 1408 patients with secondary ASD were treated at the National Amosov Institute of Cardiovascular Surgery of the National Academy of Medical Sciences of Ukraine. Of these, 54 patients who had AF and underwent the CA procedure were included in group 1 of our study. There were 36 (66.7%) men and 18 (33.3%) women aged 24-76 years (mean age 61.4 ± 9.8 years). Four (9.3%) patients had persistent AF and 50 (90.7%) patients had paroxysmal AF. Fifty-six patients with paroxysmal or persistent AF and with the comparable age, duration of symptoms and associated pathology but without ASD were examined as group 2. The type and results of surgical interventions were analyzed according to surgical reports. The results of the treatment and QoL were assessed using the Atrial Fibrillation Effect on Quality-of-Life (AFEQT) questionnaire during the follow-up period 1, 2 and 3 months after the procedure.Results. Pulmonary vein isolation was performed in all 54 (100%) patients of the group 1, as well as cavotricuspid isthmus ablation in 26 (48.2%) cases, cavotricuspid isthmus ablation and left atrial linear ablation in 2 (3.6%) cases. Type, length and complication of the procedure were comparable to those in the group 2. Fourty-four (81.5%) patients with ASD were free from AF 3 months after procedure, and their results did not differ from those obtained in the group 2 (p > 0.05). Average QoL indicators according to AFEQT significantly improved in both groups of patients who underwent CA. The differences in post-treatment QoL between patients of both groups were insignificant (p > 0.05).Conclusions. CA was found to be safe and beneficial in patients with AF and secondary ASD. The rate of procedural complications and cure rate in patients with AF and secondary ASD (81.5%) were compatible to those in patients without ASD (80.5%). AF has negative effect on the main indicators of the patient’s life. In patients with secondary AF with ASD who underwent CA, a significant improvement in AF symptoms and QoL according to the AFEQT questionnaire (total score 56.1 ± 2.7 before the procedure vs. 78.7 ± 4.0 at follow-up) was noted.